Histogen Layers Contributing to Adventitious Bud Formation Are Determined by their Cell Division Activities - Nabeshima, Tomoyuki; Yang, Soo-Jung; Ohno, Sho; Honda, Keita; Deguchi, Ayumi; Doi, Motoaki; Tatsuzawa, Fumi; Hosokawa, Munetaka (Frontiers in Plant Science, 2017)
Saintpaulia ionantha is propagated by adventitious buds in horticulture, and periclinal chimeric cultivars are usually difficult to propagate. However, some periclinal chimeric cultivars can be propagated with adventitious buds, and the mechanism of which has been unknown. Striped flower cultivars “Kaname”, “Concord”, and “Monique” were used to investigate what causes flower color separation in adventitious shoot-derived plants by tissue culture. These cultivars were revealed to have mutated flavonoid 3', 5' hydroxylase (SiF3'5'H), WDR1 (SiWDR1), or flavonoid 3 hydroxylase (SiF3H), respectively, in their L1 layer. From our previous study using “Kaname”, all flowers from adventitious shoots were colored pink, which was the epidermal color of mother plants’ flowers. We used “Concrd” and “Monique” from which we obtained not only monochromatic-colored plants the same as the epidermal color of mother plants, but also plants with a monochromatic colored plants, same as the subepidermal color, and a striped flower color the same as mother plants. Histological observations revealed that epidermal cells divided actively at 14 d after culture and they were involved in the formation of adventitious shoots in the cultured leaf segments of “Kaname”. On the other hand, in “Concord” and “Monique”, the number of divided cells in the subepidermis was rather higher than that of epidermal cells, and subepidermal cells were sometimes involved in shoot formation. In addition, the plant and leaf size of L1-derived plants from “Concord” and “Monique” were non-vigorous and smaller than those derived from the subepidermal layer. In conclusion, periclinal chimeric cultivars of Saintpaulia can be divided into two types. One type has a high cell division activity in the L1 layer, from which only single flower-colored plants derived from L1 can be obtained as adventitious shoots. Another type has a low cell division activity in the L1 layer, from which striped flower-colored plants the same as mother plants derived from several layers including L1 can be obtained as adventitious shoots. In the periclinal chimeric cultivar capable of propagation with adventitious shoots, the possibility was shown that cells in the L2 layer could form shoots by involving cells of the L1 layer with a low division activity.